Weak links : fragile states, global threats, and international security - Patrick, Stewart (Oxford university press, 2011)
Conventional wisdom among policymakers in both the US and Europe holds that weak and failing states are the source of the world's most pressing security threats today. However, as this book shows, our assumptions about the threats posed by failed and failing states are based on false premises